Binding free energy calculations on E‐selectin complexes with sLex oligosaccharide analogs. (21st September 2016) - Barra, Pabla A.; Ribeiro, António J. M.; Ramos, Maria J.; Jiménez, Verónica A.; Alderete, Joel B.; Fernandes, Pedro A.
Abstract : Molecular dynamics simulations and binding free energy calculations were employed to examine the interaction between E‐selectin and six structurally related oligosaccharides including the physiological ligand sialyl Lewis x. Molecular dynamics simulations revealed that sialyl Lewis x and its mimics share a common binding region and similar interactions with E‐selectin involving the formation of hydrogen bonds with Glu80, Asn82, Asn83, Arg97, Asn105, Asp106, and Glu107 residues and electrostatic contacts with Ca 2+ and the positively charged Lys111 and Lys 113 residues. Regarding binding free energy calculations, the performance of the rigorous but computationally expensive pathway methods TI, BAR, and MBAR was compared to the less rigorous but faster end‐point methods MM/PBSA and MM/GBSA aimed at identifying a suitable approach to deal with the very subtle binding free energy differences within the ligands under study. All methods succeeded in predicting increased binding affinities for sialyl Lewis x analogs compared to the native ligand with absolute errors <1 kcal/mol. The best correlation with experimental data was obtained by TI ( r 2  = 0.84), followed by MBAR ( r 2  = 0.80), BAR ( r 2  = 0.73), MM/PBSA ( r 2  = 0.73) and MM/GBSA ( r 2  = 0.47). These results provide valuable information to increase understanding about E‐selectin–oligosaccharide interactions and conduct further research aimed at designing novel ligands targeting this protein. Abstract : Binding free energy calculations were employed to examine the interaction between E‐selectin and six oligosaccharide ligands. The accuracy of TI, BAR, MBAR, MM/PBSA, and MM/GBSA methods was assessed showing that all methods succeeded in accounting for an increased binding affinity for thesLe x analogs toward E‐selectin compared to the native ligand, being TI the method with the best performance.